Suicide as a Form of Resistance in Achebe's Things Fall Apart (1958): A Psychoanalytical Study - LAKLOUKA, Leila; MAGROUD, Roumaissa (جامعة الوادي - University of Eloued, 2023)
تهدف الدراسة الحالية إلى التحقيق في فعل الانتحار كشكل من أشكال المقاومة في رواية الكاتب تشينوا أتشيبي " الأشياء تتداعى" ((1958 من منظور التحليل النفسي. تقدم هذه الاطروحة لمحة عامة عن مفهوم المقاومة وأشكالها في التحليل النفسي. كما تقدم الدراسة تحليلًا تاريخيًا وصفيًا تحليليًا لمختلف أشكال المقاومة في الرواية. على وجه الخصوص، يستكشف عوامل التحليل النفسي الكامنة وراء انتحار أوكونكو وكيف قاوم مجتمعه الاستعمار. وفقًا لذلك، تستخدم هذه الدراسة نهج التحليل النفسي لتفسير اوكونكو وعمله الانتحاري. وبالتالي، تكشف هذه الدراسة عن الدلائل التالية: أولاً، أوكونكو، بطل الرواية، يعكس طبيعته المتعصبة التي لن تسمح له أبدًا بالاستسلام لأسلوب الحياة الاستعماري. ثانيًا، تدل مقاومة أوكونكو الانتحارية على إحباطه من كونه نسخة من والده أونوكا. ثالثًا، أثبتت الدراسة أن الانتحار هو نتيجة القمع الذي دفع أوكونكو دون وعي إلى الانتحار كوسيلة دفاع. تمت تغطية هذا بوضوح في عمل أتشيبي من خلال تصوير وصف مفصل لشخصية أوكونكو قبل وأثناء الهيمنة الاستعمارية. The present study aims to investigate the action of suicide as a form of resistance in Chinua Achebe's Things Fall Apart (1958) from a psychoanalytic perspective. This dissertation presents an overview of the concept of resistance and its forms in psychoanalysis. The study also provides a historical and descriptive analytical analysis of the different forms of resistance in the novel. In particular, it explores the psychoanalytical factors behind, the protagonist, Okonkwo' suicide and how his society has resisted colonialism. Accordingly, this research uses a psychoanalytical approach to interpret Okonkwo and his action of suicide. Consequently, the study addresses the following points first, Okonkwo, the protagonist of the novel, reflects his scholasticism nature that does not permit him to surrender to the colonial lifestyle. Secondly, Okonkwo's suicidal resistance signifies his frustration of being the version of his father's Unoka. Thirdly, the study proves that suicide is the result of the repressions that leads Okonkwo unconsciously to commit suicide as a defence. This is clearly covered in Achebe's work through depicting a detailed description of Okonkwo's character before and during the colonial domination
Master’s Degree in Literature and Civilization
Keywords: تشينوا أتشيبي، التحليل النفسي، المقاومة، الانتحار، الأشياء تتداعى; Chinua Achebe, psychoanalysis, resistance, suicide, Things Fall Apart